MANGANESE’S EFFECT IN THE SHEET APOPLAST HIBISCUS SABDARIFFA L. VAR SABDARIFFA FOR 10 DAYS - Younes, Mavoungou Ange; Nicaise, Lepengue Alexis; Bertrand, M’Batchi (European Scientific Journal, ESJ, 2015)
Young shoots of sorrel leaves (Hibiscus sabdariffa L. var sabdariffa) were cultured in chamber for 10 days. They were submitted to the effect of manganese concentration 0,3μM per day for studying the accumulation and the toxicity of the ore in the apoplast of leaves. The results show that Mn is accumulated in the leaves during the 10 days of experiment; the number of brown spots and callose synthesis increase during the 10 days of experience. In the leaves, the antioxidants activities Guaiacol-POD and NADP-POD are high during exposure to Mn. They are raised from fifth to ninth days for Guaicol-POD and the fifth to the seventh day of the ninth and tenth days for the NADP-POD. The activity of Guaiacol-POD and NADP-POD is evaluated to monitor their detoxification response to Mn exposure level in the leave. This correlates with the reduction in the rate of H2O2 and NADH. The Leaves of sorrel shoots have the ability to accumulate and tolerate 0,3uM Mn during 10 days of exposure by inducing the synthesis of callose and controlling the rate of Guaiacol-POD and NADP-POD.